2014
DOI: 10.1371/journal.pone.0109761
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Diversity Similarities in Periodontal Pockets and Atheromatous Plaques of Cardiovascular Disease Patients

Abstract: Background and ObjectiveThe immune and infectious alterations occurring in periodontitis have been shown to alter the development and severity of cardiovascular disease. One of these relationships is the translocation of oral bacteria to atheroma plaques, thereby promoting plaque development. Thus, the aim of this study was to assess, by 16s cloning and sequencing, the microbial diversity of the subgingival environment and atheroma plaques of patients concomitantly suffering from periodontitis and obstructive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 55 publications
0
72
0
1
Order By: Relevance
“…Furthermore, F. nucleatum subsp. animalis is part of the microbial signature in early detection of colorectal cancer (49) and the only fusobacterial species / subspecies found to overlap between the microorganisms isolated from the periodontal pocket and the atheromatous plaque in cardiac disease patients (50). Our finding of a strong association of F. nucleatum subsp.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, F. nucleatum subsp. animalis is part of the microbial signature in early detection of colorectal cancer (49) and the only fusobacterial species / subspecies found to overlap between the microorganisms isolated from the periodontal pocket and the atheromatous plaque in cardiac disease patients (50). Our finding of a strong association of F. nucleatum subsp.…”
Section: Discussionmentioning
confidence: 99%
“…Porphyromonas gingivalis is an anaerobic bacterium (1) that is linked with periodontal disease (24) and multiple systemic diseases (57). In previous studies (811), P. gingivalis strains have shown a variety of pathogenic phenotypes in vitro and in vivo , but underlying genetic mechanisms are poorly defined.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Patients with uncontrolled diabetes were excluded from the current study because studies reported an association between type 2 diabetes and periodontitis (20). In the present study, participants with type 2 diabetes and an HbA1c level less than 7% were included.…”
Section: Discussionmentioning
confidence: 99%